What kind of urban–rural basic public services can affect the urban–rural income gap?–an analysis of FsQCA based on the TOE framework - He, Qianqian; Dong, Tiantian; Gadan, Cairang (Frontiers in Public Health, 2025)
IntroductionThe urban–rural income gap and the non-equalization of basic public services constitute the core contradiction in China’s urban–rural development.MethodsThis study employs the fsQCA method based on the TOE framework to determine how technological, organizational, and environmental conditions collectively shape the urban–rural income gap in China’s Yangtze River Delta region.ResultsThe findings reveal three distinct configurations of high income disparity and three distinct configurations of non-high income disparity, emphasizing that no single factor is indispensable. Rather, combinations are crucial. High-disparity configurations manifest through three divergent pathways: dual squeezes from fiscal constraints and lagging digital infrastructure; structural disconnect between economic growth and digitalization; and cyclical lock-in between low-level economies and public service shortages. Non-high-disparity configurations emerge via three equivalent pathways: factor rebalancing driven by high economic output; cross-regional coordination through institutional optimization and digital empowerment; and compensatory mechanisms based on fiscal resilience and governance innovation.DiscussionThe study offers recommendations for basic public service allocation across cities in China’s three major regions, holding significant implications for the integrated urban–rural development of China.